Heterogeneous preferences for agricultural landscape improvements in southern Finland - Grammatikopoulou, Ioanna; Pouta, Eija; Salmiovirta, Maija; Soini, Katriina (Elsevier, 2012)
In planning landscape-related policy, such as agri-environmental measures, the European Landscape Convention emphasizes the need to account for the benefits that the population and various stakeholder groups obtain from the landscape. In this study, a choice experiment was employed to evaluate a programme that provides certain landscape attributes in a typical agricultural area. The data from a municipality-level case study in southern Finland revealed that the most valued attributes were the renovation of production buildings and the presence of grazing animals. A latent class model with covariates indicated the existence of heterogeneous preferences regarding the landscape attributes, with attitude variables being significant determinants of heterogeneity. One in five of the respondents even perceived disutility from changing the level of landscape attributes. Our findings have implications for integrating landscape planning in agri-environmental measures, such as supporting organic animal husbandry, which guarantees the presence of animals outside in the agricultural landscape.
Keywords: Ma; maatalousmaisema; maisemasuunnittelu; agricultural landscape; landscape design; choice experiment; latent class; heterogeneity; agricultural landscape